Psycho-Theological Learning Model to Improve Mental Resilience in Muslim Adolescents - Muhammad Zamzam; Winsidi Winsidi (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme)
This study was conducted at STIT Muaraenim, South Sumatra, Indonesia, specifically within the Islamic education setting of Madrasah Aliyah, where psychotheological learning practices were implemented. The research utilized a qualitative approach with a phenomenological design to explore the lived experiences of Muslim adolescents undergoing such learning. Data were sourced from purposively selected teachers and students actively engaged in faith-based character education programs. To ensure data richness, the study employed triangulated collection methods including in-depth semi-structured interviews, participatory classroom observations, and document analysis comprising lesson plans, student portfolios, and reflective teacher notes. Thematic analysis was used to interpret the data, enabling a deep understanding of the psychological and theological interactions occurring in the learning process. Findings reveal that integrating Islamic theological concepts with psychological reflections enhances students’ mental resilience, promotes religious optimism, and nurtures a stable self-concept. Teachers functioned as both spiritual facilitators and emotional companions, while a spiritually nourishing learning environment proved pivotal. The study contributes to the growing body of knowledge on Islamic educational innovation by proposing psychotheological learning as a transformative pedagogical model to foster psychological strength and spiritual depth among Muslim adolescents.